2006
DOI: 10.1128/mmbr.00048-05
|View full text |Cite
|
Sign up to set email alerts
|

IS CR Elements: Novel Gene-Capturing Systems of the 21st Century?

Abstract: SUMMARY “Common regions” (CRs), such as Orf513, are being increasingly linked to mega-antibiotic-resistant regions. While their overall nucleotide sequences show little identity to other mobile elements, amino acid alignments indicate that they possess the key motifs of IS91-like elements, which have been linked to the mobility ent plasmids in pathogenic Escherichia coli. Further inspection reveals that they possess an IS91-like origin of replication and termination sites (terIS), and therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
481
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 525 publications
(511 citation statements)
references
References 109 publications
(180 reference statements)
13
481
0
9
Order By: Relevance
“…In this study, no tet genes were detected in any intI1 gene cassette arrays, which was consistent with previous studies (Toleman et al 2006). However, our previous work found that tet(A), tet(C), and tet(G) were positively correlated with intI1, which was assumed to be related with the insertion sequence common region (ISCR), a newly highlighted complex integron element which can integrate non-cassette resistance genes and combine with intI1 to form complex integrons (Toleman et al 2006;Liu et al 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, no tet genes were detected in any intI1 gene cassette arrays, which was consistent with previous studies (Toleman et al 2006). However, our previous work found that tet(A), tet(C), and tet(G) were positively correlated with intI1, which was assumed to be related with the insertion sequence common region (ISCR), a newly highlighted complex integron element which can integrate non-cassette resistance genes and combine with intI1 to form complex integrons (Toleman et al 2006;Liu et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…However, our previous work found that tet(A), tet(C), and tet(G) were positively correlated with intI1, which was assumed to be related with the insertion sequence common region (ISCR), a newly highlighted complex integron element which can integrate non-cassette resistance genes and combine with intI1 to form complex integrons (Toleman et al 2006;Liu et al 2012). In the present study, the abundance of intI1 and ISCR1 increased after OTC exposure, indicating that they may perform certain gene transfer functions under high OTC selection pressure, which requires more research.…”
Section: Discussionmentioning
confidence: 99%
“…This result implied that there may be other mechanisms responsible for bacterial resistance. Resistance to antibiotics could be due to chromosome mutation, lack of drug penetration, or resistance genes that were located in the chromosome or related to other mobile genetic elements such as insertion sequences, transposons and plasmids [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first instance where a 16S RMTase gene was found in association with ISCR2. ISCR2 is usually found intact upstream of a resistance gene, while the second copy downstream is typically truncated (14). Since ISCR2 possesses a KpnI restriction site, we were not able to assess whether the two copies of ISCR2 were intact or not.…”
Section: Figmentioning
confidence: 99%
“…ISCR2 is an IS91-like transposable element which is found in association with various resistance genes, including those for sulfonamide, trimethoprim, and florfenicol (14), and also tetracycline and cephalosporin (15,16). It is believed to facilitate mobilization of the genetic elements downstream.…”
Section: Figmentioning
confidence: 99%